2020
DOI: 10.1177/2158244020953179
|View full text |Cite
|
Sign up to set email alerts
|

Green Behavior and Financial Performance: Impact on the Malaysian Fashion Industry

Abstract: The dogma of conscious environmental behavior has laid the paradigm for sustainable consumer behavior. Modern-day corporates have introduced innovative business models to add a new value to manage fluctuations in consumer behaviors and rejuvenate their financial performance. Similarly, in fashion industry, textile firms have warmly embraced the new business models and widely adopted environmental management systems (EMSs) to contribute to environmental sustainability. This research aims to explore eco-consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 93 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Ali et al [37] Research on Malaysian sustainable fashion focussed on sustainable fashion consumption and environmental involvement. The Malaysian government-led Green Technology Corporation (MGTC) initiative is expected to promote sustainable development by establishing quotas for green product production and in various industries.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…Ali et al [37] Research on Malaysian sustainable fashion focussed on sustainable fashion consumption and environmental involvement. The Malaysian government-led Green Technology Corporation (MGTC) initiative is expected to promote sustainable development by establishing quotas for green product production and in various industries.…”
Section: Summary Of Key Findingsmentioning
confidence: 99%
“…For instance, in Malaysia, consumers are reported to have low awareness [15,17]. Furthermore, studies on fashion sustainability are still lacking in Malaysia [18]. This is the gap that this study will address.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The studies of this cluster investigated how different sustainable initiatives affect corporate performance (Chan et al, 2020;Saha et al, 2021;Sudusinghe & Seuring, 2020;Wong & Ngai, 2021;Yang & Jang, 2020). In particular, Ali et al (2020) revealed that fashion companies that successfully implemented ISO 14001 environmental management system (EMS) reported substantial efficiency improvements compared to companies that have not yet EMS.…”
Section: Impact Of Sustainability Initiatives On Corporate Performancementioning
confidence: 99%